2015
DOI: 10.1063/1.4915627
|View full text |Cite
|
Sign up to set email alerts
|

Lattice parameters and Raman-active phonon modes of β-(AlxGa1−x)2O3

Abstract: We present X-ray diffraction and Raman spectroscopy investigations of a (100)-oriented (AlxGa1–x)2O3 thin film on MgO (100) and bulk-like ceramics in dependence on their composition. The thin film grown by pulsed laser deposition has a continuous lateral composition spread allowing to determine precisely the dependence of the phonon mode properties and lattice parameters on the chemical composition. For x < 0.4, we observe the single-phase β-modification. Its lattice parameters and phonon energies depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 18 publications
5
38
0
1
Order By: Relevance
“…Some exception can be observed for x > 0.4, which we can relate to the occurrence of c-phase material. 32 The general lineshape resembles that of pure b-Ga 2 O 3 ; 12,14,15 thus, we conclude that the materials' electronic structure is dominantly b-Ga 2 O 3 -like for all Al concentrations investigated. A clear blue-shift of all absorption features can be observed as expected due to the much larger band gap of a-and c-Al 2 O 3 of %9 eV.…”
Section: B Dielectric Function and Absorption Coefficientmentioning
confidence: 80%
See 3 more Smart Citations
“…Some exception can be observed for x > 0.4, which we can relate to the occurrence of c-phase material. 32 The general lineshape resembles that of pure b-Ga 2 O 3 ; 12,14,15 thus, we conclude that the materials' electronic structure is dominantly b-Ga 2 O 3 -like for all Al concentrations investigated. A clear blue-shift of all absorption features can be observed as expected due to the much larger band gap of a-and c-Al 2 O 3 of %9 eV.…”
Section: B Dielectric Function and Absorption Coefficientmentioning
confidence: 80%
“…The increase of the transition energies, besides the effect of Al incorporation on the electronic structure, also resembles the behaviour of the lattice constants and the phonon modes. 32 Especially, the bowing observed for the thin film in the a-lattice constant, which we relate to internal strain, can be considered to be partially responsible for the bowing observed in the x-dependence of the transition energies. As a general trend, the broadening parameter of the TcLo function increases with the increase in transition energy from %0:2 eV to %1:5 eV, but does almost not depend on x.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…[9][10][11][12] Therefore, it has been widely employed in semiconductors. Kranert et al 13 have reported Raman spectra of (AlGa) 2 O 3 films with different Al content (0-0.55) at room temperature. However, in contrast to the comprehensive investigation of temperature effect of Raman scattering for other semiconductors, 14,15 temperature dependence of phonon behavior in β-(AlGa) 2 O 3 thin films has not been reported up to now.…”
Section: Introductionmentioning
confidence: 99%